2003
DOI: 10.1053/jhep.2003.50033
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of hepatocyte protection against hypoxic injury by atrial natriuretic peptide

Abstract: Atrial natriuretic peptide (ANP) reduces ischemia and/or reperfusion damage in several organs, but the mechanisms involved are largely unknown. We used freshly isolated rat hepatocytes to investigate the mechanisms by which ANP enhances hepatocyte resistance to hypoxia. The addition of ANP (1 mol/L) reduced the killing of hypoxic hepatocytes by interfering with intracellular Na ؉ accumulation without ameliorating adenosine triphosphate (ATP) depletion and pH decrease caused by hypoxia. The effects of ANP were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 36 publications
0
27
2
Order By: Relevance
“…Here, we show that changes in pHi exhibited in response to physiological concentrations of ANP can be responsible for ROS production through the activation of p38 MAPK and PLD. Since experimental evidences [46] describe the ability of ANP to inhibit cell growth, our data support the possibility that ROS production may be involved in the mechanism by which ANP inhibits HepG2 cell growth, by necrosis [47] Finally, our findings appear partially in disagreement with previous reports showing the ANP ability to reduce liver ischemia/reperfusion injury and improving hepatocytes resistance to oxidative stress [48]. It should not be surprising that ANP elicits different effects.…”
Section: Discussioncontrasting
confidence: 55%
“…Here, we show that changes in pHi exhibited in response to physiological concentrations of ANP can be responsible for ROS production through the activation of p38 MAPK and PLD. Since experimental evidences [46] describe the ability of ANP to inhibit cell growth, our data support the possibility that ROS production may be involved in the mechanism by which ANP inhibits HepG2 cell growth, by necrosis [47] Finally, our findings appear partially in disagreement with previous reports showing the ANP ability to reduce liver ischemia/reperfusion injury and improving hepatocytes resistance to oxidative stress [48]. It should not be surprising that ANP elicits different effects.…”
Section: Discussioncontrasting
confidence: 55%
“…These include studies from isolated hepatocytes that suggest a preconditioning effect limiting increases in [Na ϩ ] i during hypoxia is mediated by NO through cGK and p38 MAPK (11) and furthermore that atrial natriuretic peptide diminishes hypoxia-induced increases in [Na ϩ ] i by a similar pathway that inhibits NHE1 (10). These results are also consistent with studies that suggest activation of p38 MAPK inhibits the response of NHE1 to angiotensin II in vascular smooth muscle cells by phosphorylating the NHE1 at serine/threonine residues located between amino acids 671 and 714 (27).…”
Section: Discussionmentioning
confidence: 99%
“…This is important because the GC-A receptor is widely distributed in many different cell types and mediates the effects of ANP and BNP in many biological functions. In addition to its role in blood pressure control, recent reports have indicated that GC-A might be critical in the regulation of other completely different physiological processes, such as cellular growth in the brain and kidney, 60 angiogenesis, 119 liver regeneration, 120 or even lipolysis in adipose tissue. 121 Second, an important and still unresolved issue is whether cGMP production by different membrane-bound versus soluble GCs is compartmentalized.…”
Section: Future Directionsmentioning
confidence: 99%